Experimental investigation on mechanical properties of banana/snake grass fiber reinforced hybrid composites. (2021) - Balaji, D.; Ramesh, M.; Kannan, T.; Deepan, S.; Bhuvaneswari, V.; Rajeshkumar, L.
Abstract: Plant fibers including banana, snake grass, ramie, hemp, jute and so on are armed with enormous advantages like less weight, reliability, recyclability and environmental friendly nature. Besides the natural composites with single fibers, composites containing more than one type of fibers (hybrid composites) render a customized material design which could be used to obtain a particular property for a particular application. Current work is an attempt to manufacture and test the snake grass (SG) and banana fibers reinforced polyester composites manufactured by hand lay-up method with random fiber orientation. Methyl ethyl ketone peroxide (MEKP) was used as the coupling agent and cobalt naphthalene (CN) as the catalyst. Relative volume fraction of the fibers was varied between 5%–25% by weight in the ratio of 1:1. Properties like tensile strength and modulus, flexural strength and modulus and compressive strength are measured for the composites by conducting the appropriate tests according to ASTM standards. Results exhibited that tensile, flexural and compressive strength increased linearly with the fiber volume fraction while tensile and flexural modulus decreased with the increase in fiber volume fraction. Fracture surface morphology was analyzed by scanning electron microscopy (SEM).